Biblioteca prisional: impressões e expectativas dos privados de liberdade do Conjunto Penal de Feira de Santana - BA - Souza, Lindaura Oliveira (2024)
The library is a space of multiple learnings. It gathers diverse collections and contributes to the formation of readers, making them endowed with knowledge, skills, autonomy, and a critical eye. Specifically in prison libraries, these play an important role in serving a public deprived of freedom and, therefore, present challenges given the complexities of experiences inserted in penitentiaries. In the present research, I propose to investigate the role of the prison library as a space for access to information and citizenship. The general objective is to analyze the contribution of the library to the resocialization process, based on the impressions and expectations of the deprived of liberty of the Conjunto Penal de Feira de Santana (CPFS). The research is qualitative in nature and has a bibliographical character and a case study. The methodology used is the case study, anchored in Yin's studies (2001), and in the discussions of Marconi and Lakatos (2009). As data generation strategies, we opted for participant observation and semi-structured interviews. As a theoretical foundation on the library, the authors Petit (2008, 2013), Milanesi (1998) and Colares and Lindemann (2015) were adopted. The theoretical foundation on education in prisons is based on Julião (2019 and 2022) and Onofre (2013 and 2022). The discussions on reading were based on Jouve (2002), Lajolo (1982 and 2000), among others. The data obtained point to the importance of the library in the democratization and dissemination of knowledge and, thus, help to ensure that the deprived of liberty have the opportunity to transform their reality. The research seeks to contribute to the discussions on libraries, reading, and resocialization.